Perindopril in Breast Milk and Determination of Breastfed Infant Exposure: A Prospective Observational Study - Leggett C; Lwin EMP; Ritchie U; Song Y; Gerber JP; Turner S; Hague WM; Stark M; Upton R; Garg S (Dove Medical Press, 2020)
Catherine Leggett,1,* Ei Mon Phyo Lwin,2,* Usha Ritchie,1 Yunmei Song,2 Jacobus P Gerber,2 Sean Turner,1 William M Hague,3,4 Michael Stark,3,5 Richard Upton,2 Sanjay Garg2 1SA Pharmacy, Women’s and Children’s Hospital, North Adelaide, SA 5006, Australia; 2School of Pharmacy and Medical Sciences, Reid Building, City East Campus, University of South Australia, Adelaide, SA 5000, Australia; 3Robinson Research Institute, University of Adelaide, North Adelaide, SA 5006, Australia; 4Obstetric Medicine, Women’s and Children’s Hospital, North Adelaide, SA 5006, Australia; 5Neonatal Medicine, Women’s and Children’s Hospital, North Adelaide, SA 5006, Australia*These authors contributed equally to this workCorrespondence: Sanjay GargCentre for Pharmaceutical Innovation and Development (CPID), School of Pharmacy and Medical Sciences, University of South Australia, Adelaide, SA 5000, AustraliaTel +61 8 830 21575Fax +61 8 830 22389Email Sanjay.Garg@unisa.edu.auObjective: This study aimed to quantify the amount of perindopril and its active metabolite perindoprilat present in breast milk and corresponding maternal and infant plasma concentrations.Design: Prospective, longitudinal, observational.Setting: Tertiary specialist paediatric and obstetric hospital in Adelaide, South Australia.Population: Breastfeeding women actively treated with perindopril for hypertensive disorders postpartum.Methods: Eight breast milk samples and a single plasma sample were collected from each participant over a 24 hrs period, and plasma samples were taken from eligible breastfed infants. Breast milk and plasma concentrations of perindopril and perindoprilat were analysed using a validated Liquid Chromatography tandem-Mass Spectrometry (LC-MS/MS) method.Main Outcome Measures: Mean breast milk concentrations of perindopril and perindoprilat, Relative Infant Dose (RID) < 10%, and Theoretical Infant Dose (TID).Results: Ten women and three infants participated in the study. The mean concentration of perindopril in breast milk for each participant ranged from 0.003 to 1.2 ng/mL and perindoprilat 0.2– 36 ng/mL. RID for perindopril was 0.0005– 0.2% and perindoprilat 0.03– 4.6%. TID for perindopril was 0.00045– 0.18 μg/kg/day and perindoprilat 0.032– 5.4 μg/kg/day. Infant plasma levels for perindopril ranged from 0.44 to 1.12 ng/mL and perindoprilat undetectable – 10.14 ng/mL. Maternal reports described normal infant growth and development.Conclusion: Infant exposure to perindopril and perindoprilat through breast milk is low. However, some infants were found to have plasma perindoprilat concentrations consistent with pharmacodynamic effects. Perindopril may be used in mothers of healthy term infants, provided the infant is carefully monitored.Keywords: perindopril, perindoprilat, LC-MS/MS, human plasma, human milk, clinical lactation, infant drug exposure